Cultural traditional and special rituals related to the health in Bugis Ethnics Indonesia - M. Fais Satrianegara; Hamdan Juhannis; Abd. Madjid H.R. Lagu; Habibi; Sukfitrianty; Syamsul Alam (Elsevier, 2021)
Objective: Health problems are complex problems the resultant of various environmental problems that are natural and man-made, socio-cultural, behavior, population, and genetics. Method: This research is a qualitative type with an ethnographic approach which is also supported by a phenomenological approach. Results: In the Ammatoa Kajang tribe, there are 4 special rituals related to health, namely Panganro (safety of the world and the hereafter and disease outbreaks), Andingingi (avoiding disasters), Allisa'Ere Tallasa (health and safety of children), and Abbole simaja (healing of diseases in children). The Towani Tolotang tribe has a Perrynyameng ritual, Sipulung ritual which aims to ask for protection, happiness, and health. Massempe attractions to test leg strength in children. Conclusions: Perceptions of the concept of illness, health, and the diversity of types of rituals used to repel disease are formed through a process of socialization which is hereditary believed and believed to be true.